Coaching People with Cardiovascular Disease to Close Their “Treatment Gaps” Reduces Hospital Utilization, Saves Lives, and Delivers Net Cost Savings Over 10 Years - Joshua Byrnes; Margarite J. Vale; Clifford Afoakwah; Pippa Grant; Sharmani Barnard (American Journal of Medicine Open)
Background: Disease management programs are an essential tool in the fight against rising prevalence and costs associated with cardiovascular disease (CVD). However, there is a lack of evidence on the long-term impact of these programs on clinical outcomes, healthcare utilization, and cost. This study presents a long-term follow up of clinical, healthcare utilization and cost, and mortality consequences of The COACH Program, a 6-month telephone delivered CVD prevention program. Methods: We conducted 10-year retrospective propensity score matched cohort study of potentially eligible participants comparing individuals that participated to those that did not receive the Program. Primary outcomes of interest were differences in mortality, private healthcare utilization and cost of private healthcare utilization sourced from private health insurance claims data. Results: Of the 24,932 potentially eligible participants, 11,988 were invited to participate in The COACH Program between July 1, 2010, and December 31, 2020. The COACH Program participants (n = 2,271) were 1:1 matched with individuals who did not participate in the Program. Participation in The COACH Program was associated with a 34% reduction in the risk of mortality (HR: 0.66, 95% CI: 0.54, 0.79), an 8% reduction in the number of hospitalizations (IRR: 0.92, 95% CI: 0.85, 0.98), and an annual reduction in healthcare costs of $1,499 (95% CI: $1,909, $1,087). Results were robust to sensitivity analyses. Conclusions: A structured 6-month telephone delivered coaching program focused on closing “treatment gaps” in people with a history of CVD saves lives and reduces hospital utilization, health care costs over 10-years follow-up.